Application of Health Education to Prevent Pre-Eclampsia Emergencies in 1st Trimester Pregnant Women - Ulaa, Mar'atun; Marlin, Riska; Yuniza, Yuniza; Azmi, Khusnul Tisa (Journal of Universal Community Empowerment Provision, 2024)
Preeclampsia is one of the main causes of maternal death throughout the world, including in Indonesia. Preeclampsia is characterized by hypertension, urine protein and edema in pregnancy, after 20 weeks of gestation. Early detection of preeclampsia is carried out to reduce the incidence and reduce the death rate and prevent severity for the mother and fetus. Health education about preeclampsia can be carried out to increase knowledge of pregnant women. The Objective of the research to increase mothers' knowledge about preeclampsia. Implementation method by providing health education using booklets to 22 pregnant women in the Pemulutan Community Health Center working area, Ogan Ilir Regency. The result of the study statistically, health education is effective in increasing respondents' knowledge about emergency prevention: preeclampsia. Pregnant women with knowledge scores before and after being given health education experienced an increase in the mean difference of 42. Health education using booklet media can increase pregnant women's knowledge about preeclampsia.